Comparative Study of Virtual Methods Used for Library Service Delivery among Librarians in Southern Nigeria Private Universities - Ilesanmi, Titilayo Comfort (International Journal of Knowledge Content Development & Technology, 2024)
This study examined the virtual methods of service delivery being deployed by librarians in private universities in Nigeria. The objective of the study was to analyse the virtual methods of service delivery among librarians and determine the predominant method used among the librarians. Survey research design was adopted for the study. Total enumeration technique was adopted for the study. A population of 181 librarians from 45 private universities in Southern Nigeria were involved. Data were gathered, analysed and presented using frequency counts, percentages, mean and standard deviation. The study found that librarians used different virtual methods of service delivery. Library website 157 (90%) and e-mail 132 (76.3%) were the prominent electronic media used by librarians while Facebook 59 (34%) and Whatsapp 57 (32.9%) were the predominant social media platforms applied for service delivery by librarians. Electronic media were more used for latest publications arrival, as well as library education and document delivery services while social media were more used for reference services and selective dissemination of information. In conclusion, virtual methods of service delivery were deployed by librarians in private universities for service delivery. In comparing the virtual methods, librarians used more of electronic media than social media to deliver services to their users. Therefore, electronic media were predominantly used than social media, many of the virtual methods were found to be underutilised while recommendations were proffered.